Evidence for TGF-β1/Nrf2 Signaling Crosstalk in a Cuprizone Model of Multiple Sclerosis - Coram Guevara; Sinay C. Vicencio; Ignacio S. Pizarro; Francisca Villavicencio-Tejo; Rodrigo A. Quintanilla; Pablo Astudillo; Estibaliz Ampuero; Rodrigo Varas; Juan A. Orellana; Fernando C. Ortiz (MDPI AG, 2024)
Multiple sclerosis (MS) is a chronic and degenerative disease that impacts central nervous system (CNS) function. One of the major characteristics of the disease is the presence of regions lacking myelin and an oxidative and inflammatory environment. TGF-β1 and Nrf2 proteins play a fundamental role in different oxidative/inflammatory processes linked to neurodegenerative diseases such as MS. The evidence from different experimental settings has demonstrated a TGF-β1-Nrf2 signaling crosstalk under pathological conditions. However, this possibility has not been explored in experimental models of MS. Here, by using the cuprizone-induced demyelination model of MS, we report that the in vivo pharmacological blockage of the TGF-β1 receptor reduced Nrf2, catalase, and TGFβ-1 protein levels in the demyelination phase of cuprizone administration. In addition, ATP production, locomotor function and cognitive performance were diminished by the treatment. Altogether, our results provide evidence for a crosstalk between TGF-β1 and Nrf2 signaling pathways under CNS demyelination, highlighting the importance of the antioxidant cellular response of neurodegenerative diseases such as MS.